Standard Operating Procedure for high throughput phenotyping using NIRS - Mbanjo-Edwige, G.; Peteti, P.; Toyinbo, S.; Ogunpaimo, K.; Nafiu, K. (International Institute of Tropical Agriculture, 2024)
The near-infrared spectroscopy is a non-destructive and rapid method for predicting the qualitative and quantitative properties of samples. The NIRS spectral regions, which are located between the visible and infrared ranges (800-2500 nm; 12500-4000 cm-1) contain a wealth of useful information. The development and optimization of NIRS prediction models could enable reliable, high-throughput, and low-cost analyses of high-value traits. Hundreds of samples could be quickly screened, and multiple parameters could be evaluated in a single test.